Reseña bibliográfica: Ruffini, Martha y Blacha, Luis E. (compiladores). Burocracia, tecnología y agro en espacios marginales, Rosario, Prohistoria, 2011. - Rodríguez Vázquez, Florencia (2012)
Fil: Fil: Rodríguez Vázquez, Florencia. CONICET; Argentina